Analysis Of The Influence Of Company Size, Corporate Good Governance And Return On Equity On Value Of Lq45 Companies Listed In Indonesian Stock Exchange - Mismiwati; Tanti Widia Nurdiani; Alfiana; Loso Judijanto; Dini Mardiani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This research aims to see whether there is an influence between the variable’s good corporate governance, return on equity, and company size simultaneously on company value. Purposive sampling was the method utilized to choose the sample for this study. All 45 LQ companies that are registered on the Indonesia Stock Exchange make up the research population. Data for this study came from literature reviews and field investigations. This study's data analysis approach makes use of a multiple regression model. This investigation employed a two-tailed test. The following conclusions can be made in light of the data gathered and the tests performed on the issue using a multiple regression model: Company size, return on equity, audit committee, managerial ownership, and institutional ownership all simultaneously and significantly affect a company's value. The value of a corporation is partly influenced by managerial ownership. The value of a corporation is not partially impacted by institutional ownership. The audit committee's impact on the value of the company is zero. The value of the company is partially impacted by return on equity. The worth of a corporation is not influenced in part by its size.